1978
DOI: 10.1016/0005-2728(78)90166-4
|View full text |Cite
|
Sign up to set email alerts
|

Electron acceptors associated with P-700 in Triton solubilized Photosystem I particles from spinach chloroplasts

Abstract: Flash-induced absorption changes of Triton-solubilized Photosystem I particles from spinach were studied under reducing and/or illumination conditions that serve to alter the state of bound electron acceptors. By monitoring the decay of P-700 following each of a train of flashes, we found that P-430 or components resembling it can hold 2 equivalents of electrons transferred upon successive illuminations. This requires the presence of a good electron donor, reduced phenazine methosulfate or neutral red, otherwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(60 citation statements)
references
References 24 publications
8
52
0
Order By: Relevance
“…This assertion is supported by the observation that reduction of the PS I sample by dithionite results in the acceleration of P-700 + decay to 265/~s (not shown). Such a -250/~s decay is diagnostic at room temperature for the backreaction between P-700 ÷ and A~ [20]. Note that similar kinetics are observed in the presence of dithionite in both the control and UV-irradiated samples.…”
Section: Dependence Of the P-700 ÷ Absorptionmentioning
confidence: 53%
“…This assertion is supported by the observation that reduction of the PS I sample by dithionite results in the acceleration of P-700 + decay to 265/~s (not shown). Such a -250/~s decay is diagnostic at room temperature for the backreaction between P-700 ÷ and A~ [20]. Note that similar kinetics are observed in the presence of dithionite in both the control and UV-irradiated samples.…”
Section: Dependence Of the P-700 ÷ Absorptionmentioning
confidence: 53%
“…However, kinetic measurements of the re-reduction of the reaction centre chlorophyll P700 have indicated that, as in bacteria, other electron carriers are also involved in the electron-transfer process [4]. We have shown that if photosystem I samples are prepared under extreme reducing conditions and frozen under illumination, a component giving rise to an EPR signal in the g = 2.00 region is reduced [5,6].…”
Section: Introductionmentioning
confidence: 84%
“…Three polypeptides with molecular weights of 18,000, 16,000, and 8,000 were suggested to be iron-sulfur proteins mediating the transfer of electrons from the primary acceptor on the 110,000 molecular weight polypeptide to soluble ferredoxin (4). Recently, an additional ironsulfur protein has been shown involved in this electron transfer (35). Iron-sulfur proteins are likely candidates for the three small polypeptides present in minute amounts in viridis-n 34.…”
Section: Discussionmentioning
confidence: 99%